2020
DOI: 10.1002/admi.201902188
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Heterogeneous Wrinkles in Metal/Polydimethylsiloxane Film System by Combination of Mechanical Loading and Heat Treatment

Abstract: dehydration, and atrophy. Controlling wrinkle morphologies including orientation, wavelength, and amplitude is very important and necessary for various practical applications.Generally, the orientation of wrinkles is determined by the stress distribution of the film. Unidirectional strain results in stripe-like wrinkles perpendicular to the strain axis [4,5] while multidirectional strain leads to disordered labyrinth-like or ordered herringbone wrinkles. [6,7] Introduction of film impurity can induce local str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 46 publications
(71 reference statements)
3
33
0
Order By: Relevance
“…Heating is another reliable way to create wrinkled patterns in bilayer systems for the compressive stress introduced to the upper stiffer film during the cooling process. [15,33] Hence, heating might also be an effective method to realize the dynamic control of wrinkled patterns and the friction property. The AFM and LFM measurements were taken in situ as the temperature rose from room temperature (25 °C) to 75 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heating is another reliable way to create wrinkled patterns in bilayer systems for the compressive stress introduced to the upper stiffer film during the cooling process. [15,33] Hence, heating might also be an effective method to realize the dynamic control of wrinkled patterns and the friction property. The AFM and LFM measurements were taken in situ as the temperature rose from room temperature (25 °C) to 75 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Surface wrinkled patterns with periodic or aperiodic topographies are widespread [ 1–4 ] due to their various and distinctive physical, [ 5,6 ] chemical, [ 7,8 ] and biotic properties, [ 9,10 ] such as human skins, blood cells, and dehydrated fruits, with random dimensions spanning across length scales from nanometers to meters. [ 11–13 ] In particular, the tunable morphologies of wrinkled surfaces enable the possibility of controlling the friction property, [ 14,15 ] thereby providing broad and fantastic potential applications in nanomechanical systems, microfluidic channels, and soft‐fingered robotics. [ 16–19 ] Recently, it has been reported that the friction of wrinkled surfaces is closely related to morphological features, including amplitude, wavelength, and orientation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-plane pre-tension induces a softening of the outward deflection of the substrate relative to the inward deflection, and hence may promote the formation of hierarchical wrinkles and periodic ridges. For a bilayer with the modulus ratio m f =m s = 200 under high pre-stretch l 0 1s = 1:75, we observe hierarchical wrinkling pattern (see Figure 5) in the form of alternating packets of large and small undulations (c) Surface morphology of a silver film sputter deposited on a PDMS substrate after heating/cooling process under prestretch and the profile of the film after annealing [40], where hierarchical wrinkles appear. [18,36,[39][40][41].…”
Section: Pre-stretch-induced Hierarchical Wrinkles and Periodic Ridgesmentioning
confidence: 94%
“…For a bilayer with the modulus ratio m f =m s = 200 under high pre-stretch l 0 1s = 1:75, we observe hierarchical wrinkling pattern (see Figure 5) in the form of alternating packets of large and small undulations (c) Surface morphology of a silver film sputter deposited on a PDMS substrate after heating/cooling process under prestretch and the profile of the film after annealing [40], where hierarchical wrinkles appear. [18,36,[39][40][41]. The surface morphology of hierarchical wrinkles is similar to the experimental measurement [40] of cross-sectional profiles of heterogeneous wrinkles in silver/PDMS bilayers (see Figure 5(c)).…”
Section: Pre-stretch-induced Hierarchical Wrinkles and Periodic Ridgesmentioning
confidence: 94%